Mītiskais Ērika Ešenvalda operas "Iemūrētie" libretā - Šuvajeva, Anna (Latvijas Universitāte, 2021)
Bakalaura darbā “Mītiskais Ērika Ešenvalda operas “Iemūrētie” libretā” ir analizēts mītiskā izmantojums Ineses Zanderes radītajā operas libretā, meklētas mitoloģisko sižetu iezīmes citos literatūras un operu libretu tekstos. Apzināti teksti un pētītas būvupura mīta sižeta dažādās interpretācijas Eiropas tautu folklorā, kā arī aprakstīts operas “Iemūrētie” librets. Analizēts būvupura mīts un tā dažādie varianti, un to izmantojums operas “Iemūrētie” libretā. Darbā secināts, ka libretiste izmantojusi vairākus tēlus un notikumus, kas raksturīgi mitoloģiskajiem sižetiem, kur aprakstīts būvupuris. Libretiste vākusi informāciju par mīta fenomenu.

The purpose of the bachelor’s thesis “The mythical aspects in the opera libretto ‘Immured’ by Eriks Esenvalds” is to present the content analysis of the use of the mythical in the opera libretto written by Inese Zandere. The thesis also focuses on searching the mythological storyline features in other literary texts and opera librettos. After identifying the texts for the analysis author of the thesis researches different story interpretations about builders’ rites that are known in the European folklore. The storyline about the builder’s rites and other versions of the myth have been analyzed seperately as well as in the opera libretto “Immured”. The bachelor’s thesis concludes that the author of libretto was influenced by the characters and events from mythological stories about sacrifice victims. Before writing the libretto the author collected information about the phenomenon of myth.
The mythical aspects in the opera libretto " Immured" by Eriks Esenvalds
Keywords: Filoloģija; opera; librets; mīts; teksts; būvupuris